Thermally stable and highly recyclable carbon fiber-reinforced polyketone composites based on mechanochemical bond formation - You, Jiwan; Lee, Young Mo; Choi, Han-Hyeong; Kim, Tae Ann; Lee, Sang-Soo; Park, Jong Hyuk (ELSEVIER SCI LTD, 2021)
Compounding polyketone (PK) with carbon fibers (CFs) can provide composites that exhibit excellent properties. However, the thermal stability of PK itself is poor, limiting practical applications at high temperatures. Herein, a novel process is proposed to improve the thermal stability of PK-based carbon fiber-reinforced polymers (CFRPs). The plasma-assisted mechanochemistry (PMC) process creates mechanochemical bonds between materials under dry conditions, reducing polymer chain mobility at high temperatures and increasing the stiffness. Compared with conventional PK-based CFRPs, PMC-processed CFRPs have significantly higher glass transition temperatures and storage modulus, resulting in improved thermal stability. The tensile strength remained >90% after annealing at 150 degrees C for 1000 h. Moreover, despite repeated thermal hysteresis, the recycled PK-based CFRPs showed tensile strength, Young's modulus, and elongation at break that were >90% of initial values. This work provides a feasible and ecofriendly strategy to expand the applications and promote repeated recycling of PK-based CFRPs.